Excitatory-inhibitory imbalance in the brain of the wobbler mouse model of amyotrophic lateral sclerosis substantiated by riluzole and diazepam. (29th September 2017) - Andreasen, Signe Rode; Lundbye, Camilla Johanne; Christensen, Tine Breckling; Thielsen, Karina Dvinge; Schmitt-John, Thomas; Holm, Mai Marie
Highlights: Drugs have distinct effects on the brain of the wobbler mouse model of ALS. Riluzole demonstrated more pronounced effects on wobbler mice compared to controls. Diazepam displayed reduced effects on wobbler individuals compared to controls. Drug effects on paired-pulses and initial facilitation during trains were comparable. Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease. So far, no cure exists, prompting studies in disease mechanisms to facilitate development of new treatment strategies. In this study, we employed the wobbler mouse model of ALS focusing on a symptomatic group of animals. We studied the neurophysiological changes conferred by riluzole or diazepam application, two drugs employed in ALS. Riluzole is an antiglutamatergic agent and the only drug to offer some effect on the life expectancy of ALS patients. To target the inhibitory system, we utilized diazepam as a GABAergic modulator. Acute brain slices were prepared from the wobbler mouse model and analyzed using extracellular field recordings in the hippocampus. During Schaffer collateral stimulation, riluzole caused a marked reduction in the paired-pulse ratio (p < 0.0001). Importantly, this reduction was more pronounced in wobbler slices (e.g. 184.2 ± 8.9% at 20 ms interval without riluzole, and 124.3 ± 9.8% in the presence of riluzole) compared to control slices (at 20 ms: from 198.7 ± 5.8% to 160.5 ± 6.7%). Diazepam caused less pronounced effects at wobbler slices and reduced the paired-pulse ratio more in control animals compared to wobbler individuals (p < 0.0001). Comparable results were obtained during trains of stimulations (10 pulses at 20 Hz). Importantly, paired-pulse ratios as well as synaptic facilitation were overall similar in control and wobbler slices, without the drugs present, indicating that the differences were only revealed pharmacologically. In summary, the present data support excitatory-inhibitory imbalances in the brain of the wobbler mouse and further consolidate this mouse as an animal model of ALS.